Creating Innovative Healthcare Apps for Dementia Patients and Caregivers - Weerasinghe H.P.E.N; Samarathunga S.R.L; Warnakulasuriyage K.H.A; Serasingha K.A.Y.E.D; Chandrasiri, Sanjeevi; Wijendra, Dinuka (International Journal of Engineering and Management Research, 2023)
The provision of appropriate care and support to elderly individuals with dementia poses significant challenges, as they often struggle to manage their health conditions due to cognitive limitations and lack of assistance. This research aims to address this problem by developing a user-friendly healthcare system that caters to the unique needs of dementia patients. The system incorporates wearable devices and a mobile app, enabling patients to monitor their health status and communicate with their healthcare team. The primary objective is to track patients' day-to-day activities, meals, exercises, critical situations, and mental health, generating comprehensive reports for doctors to assess their overall well-being. Additionally, the research focuses on leveraging artificial intelligence to enhance patients' moods through personalized audio and video clips, utilizing image processing to detect facial expressions. Machine learning algorithms are employed to provide personalized meal plans based on data collected from IoT devices. Moreover, a warning system is developed to promptly alert both the patient and the nearest hospital in emergency situations using IoT data. The research also emphasizes automating the generation of monthly health reports, which are shared with the patient's doctor for review. By showcasing the potential of these technologies, this research aims to improve the outcomes of dementia patients, enhance healthcare efficiency, and deliver personalized care.